Elucidating the sponge stress response; lipids and fatty acids can facilitate survival under future climate scenarios. (10th April 2018) - Bennett, Holly; Bell, James J.; Davy, Simon K.; Webster, Nicole S.; Francis, David S.
Abstract: Ocean warming (OW) and ocean acidification (OA) are threatening coral reef ecosystems, with a bleak future forecast for reef‐building corals, which are already experiencing global declines in abundance. In contrast, many coral reef sponge species are able to tolerate climate change conditions projected for 2100. To increase our understanding of the mechanisms underpinning this tolerance, we explored the lipid and fatty acid (FA) composition of four sponge species with differing sensitivities to climate change, experimentally exposed to OW and OA levels predicted for 2100, under two CO2 Representative Concentration Pathways. Sponges with greater concentrations of storage lipid, phospholipids, sterols and elevated concentrations of n ‐3 and n ‐6 long‐chain polyunsaturated FA (LC PUFA), were more resistant to OW. Such biochemical constituents likely contribute to the ability of these sponges to maintain membrane function and cell homeostasis in the face of environmental change. Our results suggest that n ‐3 and n ‐6 LC PUFA are important components of the sponge stress response potentially via chain elongation and the eicosanoid stress‐signalling pathways. The capacity for sponges to compositionally alter their membrane lipids in response to stress was also explored using a number of specific homeoviscous adaptation (HVA) indicators. This revealed a potential mechanism via which additional CO2 could facilitate the resistance of phototrophic sponges to thermal stress through an increased synthesis of membrane‐stabilizing sterols. Finally, OW induced an increase in FA unsaturation in phototrophic sponges but a decrease in heterotrophic species, providing support for a difference in the thermal response pathway between the sponge host and the associated photosymbionts. Here we have shown that sponge lipids and FA are likely to be an important component of the sponge stress response and may play a role in facilitating sponge survival under future climate conditions. Abstract : Elucidating the sponge stress response; lipids and fatty acids can facilitate survival under future climate scenarios. Some of the previously uncharacterized cellular support features and biochemical responses observed by sponges exposed to ocean warming and ocean acidification. Possible stress response pathways and mechanisms via which observed responses might facilitate sponge tolerance are also provided. Sponge species are Cymbastela coralliophila (top left), Carteriospongia foliascens (top right), Rhopaloeides odorabile (bottom right) and Stylissa flabelliformis (bottom left). Blue = thermally resistant species, red = thermally sensitive species, green = phototrophic species, orange = heterotrophic species, black = species‐specific responses. FA = fatty acid, LC PUFA = long‐chain polyunsaturated fatty acid, ARA = arachidonic acid.